Criminal Law Implication on the Spread of Hoax News on Social Media in the Perspective of ITE Law - Arianus Harefa; Fariaman Laia (Journal of Strafvordering Indonesian, 2024)
The phenomenon of hoaxes on social media in Indonesia is a major challenge in the digitalization era, with false information often targeting sensitive issues and potentially triggering public unrest. The increase in internet users accelerates and expands the reach of hoaxes, especially on politics, health, and racial issues, which can lead to social instability. To combat this, the Electronic Information and Transaction Law (ITE Law) provides the legal basis for taking action against perpetrators of hoaxes, particularly through Article 28 Paragraph (1), which prohibits the dissemination of false information that is disturbing. However, the effectiveness of the ITE Law is still hampered by the unclear definition of hoaxes, technical challenges in tracking down perpetrators who often use fake identities, and limited capacity of law enforcement. On the other hand, people's low digital literacy increases the risk of inadvertently spreading hoaxes. Therefore, a normative juridical approach is used in this study to analyze the ITE Law regulation and its challenges, as well as to identify the need for integration between law enforcement and improving digital literacy as a strategic step in reducing the spread of hoaxes and maintaining social stability